Human Embryo Development and Pregnancies in an Homologous Granulosa Cell Coculture System - Fabbri, Raffaella (Kluwer Academic Publishers-Plenum Publishers, 2000)
Purpose: Our purpose was to determine the effects of thecoculture of embryos on human granulosa cells (GCs) inpatients in the first cycle of IVF-ET treatment and in patientswith repeated implantation failures and to investigate thepresence of specific proteins in a 48-hr GC conditionedmedium and the GC ultrastructural characteristics. Methods: Eighteen patients with tubal or idiopathicinfertility were enrolled in this study: 7 patients (Trial 1) were inthe first cycle of IVF-ET treatment and 11 patients (Trial 2)had repeated implantation failures (one to five). Embryosfrom each patient were cocultured randomly either onhomologous granulosa cells or on a conventional culturemedium. Results: At the end of the coculture period (day 5 or 6),50% of the embryos (Trial 1) reached the blastocyst stage,with respect to 35% in Trial 2. The pregnancy rate perretrieval was 14.2 and 9%, respectively, in Trial 1 and inTrial 2. Many conditioned media showed proteins of 24–29kDa. and some of them showed additional proteins of 90kDa. The ultrastructural analysis of GCs showed healthy,metabolically active, protein-synthesizing, and mostlysteroidogenic cells. Conclusions: GC cultures improve embryo development butnot pregnancy rates both in Trial 1 and in Trial 2.